The Texas calaboose and other forgotten jails - Moore, William E. (Tarleton State University Southwestern studies in the humanities, 2019)
"A calaboose is, quite simply, a tiny jail. Designed to house prisoners only for a short time, a calaboose could be anything from an iron cage to a poured concrete blockhouse. Easily constructed and more affordable for small communities than a full-sized building, calabooses once dotted the rural landscape. Though a relic of a bygone era in law enforcement and no longer in use, many calabooses remain in communities throughout Texas, often hidden in plain sight. In The Texas Calaboose and Other Forgotten Jails, William E. Moore has compiled the first guidebook to extant calabooses in Texas. He explores the history of the calaboose, including its construction, use, and eventual decline, but the heart of the book is in the alphabetically arranged photo tour of calabooses across the state. Each entry is accompanied by a vignette describing the unique features of the calaboose at hand, any infamous or otherwise memorable occupants, and the state of the calaboose at present. This definitive guide to tiny Texas jails serves as a record of a unique and disappearing feature of our heritage."--Provided by publisher